Circular RNAs in Lung Cancer: Recent Advances and Future Perspectives - Chen, Huan-Huan; Zhang, Tie-Ning; Wu, Qi-Jun; Huang, Xin-Mei; Zhao, Yu-Hong (Frontiers in Oncology, 2021)
Globally, lung cancer is the most commonly diagnosed cancer and carries with it the greatest mortality rate, with 5-year survival rates varying from 4–17% depending on stage and geographical differences. For decades, researchers have studied disease mechanisms, occurrence rates and disease development, however, the mechanisms underlying disease progression are not yet fully elucidated, thus an increased understanding of disease pathogenesis is key to developing new strategies towards specific disease diagnoses and targeted treatments. Circular RNAs (circRNAs) are a class of non-coding RNA widely expressed in eukaryotic cells, and participate in various biological processes implicated in human disease. Recent studies have indicated that circRNAs both positively and negatively regulate lung cancer cell proliferation, migration, invasion and apoptosis. Additionally, circRNAs could be promising biomarkers and targets for lung cancer therapies. This review systematically highlights recent advances in circRNA regulatory roles in lung cancer, and sheds light on their use as potential biomarkers and treatment targets for this disease.